Suicide risk among female breast cancer survivors: A population–based study - Shi, Jian; Yang, Yongping; Guo, Yu; Ren, Wu (Frontiers in Oncology, 2022)
Background: Breast cancer is the most common cancer type for females and has the highest relative number of suicide cases among female-specific cancers. This study aimed to demonstrate suicide rates and changing trends and to identify risk factors for suicide among female breast cancer survivors. Methods: Data were derived from the surveillance, epidemiology, and end results database for women diagnosed with breast cancer from 2000 to 2017. Mortality rate and Standardized mortality ratios (SMRs) were calculated to describe the incidence rate and trend of suicide among female breast cancer survivors. Gray’s test and cumulative incidence function (CIF) curves were used to assess difference of cumulative suicide incidence in subgroups. Multivariate Fine-Gray competing risk model was used to identify risk factors for individual patients and nomogram model was used to estimate the probability of suicide. Result: There were 414 suicide cases among 638,547 female breast cancer survivors observed for 5,079,194 person-years,. Female breast cancer survivors had a higher risk of suicide than the general population (SMR = 1.19; 95% CI (1.08–1.31)). Based on the result of Fine-Gray competing risk models, age group (50-70 vs <50: HR=0.65, 95% CI:0.52-0.80; >70 vs <50: HR=0.22, 95% CI:0.15-0.32), race/ethnicity (black vs white: HR= 0.20, 95% CI: 0.11-0.36; other race/ethnicity vs white: HR= 0.67, 95% CI: 0.46-0.97), marital status (separated vs married: HR= 1.50, 95% CI: 1.16-1.94; single vs married: HR= 1.70, 95% CI: 1.31-2.20), stage (distant vs regional: HR= 0.30, 95% CI: 0.14-0.63), radiotherapy (Yes vs No/Unknown: HR= 0.62, 95% CI: 0.49-0.77), and molecular subtypes (HER-2 vs Luminal B (HR= 2.53, 95% CI: 1.10-5.82), TNBC vs Luminal B (HR= 2.11, 95% CI: 1.01-4.42)) were independent predictors of suicide among female breast cancer patients. A nomogram was constructed to predict the suicide probability for individual survivors with a C-index of 0.62 (95%CI: 0.59-0.66). Conclusion: Female breast cancer survivors with younger age, white race/ethnicity, unmarried status, regional stage, HER-2 or TNBC subtype, and no radiotherapy performed were more likely to commit suicide. The clinicians and family members should pay more attention to patients with high risk factors of suicide to decrease the mortality rate.